WHAT THINKS THE UNIVERSITY’S STUDENTS ABOUT PROPAGATION OF LIGHT IN THE VACUUM? - Djanette, Blizak; Fouad, Chafiqi; Djamel, Kendil. (European Scientific Journal, ESJ, 2013)
This study aims to study the conceptions of university students related to the notion of propagation of light in a vacuum. In order to fulfill our aim, a case study research method was used in the study, whose sample consisted of 321 Algerian undergraduates in different levels at science faculty (before and after the optics courses). The data were collected through a test comprising three questions. The results have indicated two students’ misconceptions concerning propagation of light in vacuum. The first one is that the light does not propagate in a vacuum. The second is that the light propagates according the horizontal direction (new misconception). The possible origins of these misconceptions are discussed and suggestions for how to prevent them are given. Also, our results suggest that university students who had a higher level of physics knowledge than their counterparts who studied only geometrical optics, they still held of the same misconceptions. Formal or traditional teaching seems helpless to facing these misconceptions.